A facile approach to enhancing the UV blocking properties of layered double hydroxides and potential application in asphalt. (October 2021) - Xu, E.; Chen, P.; Wang, G.; Li, K.; Lin, Y.
Abstract: Defect-structured Zna Mgb Alc layered double hydroxides (d-Zna Mgb Alc -LDHs) with varying Mg/Zn ratios have been prepared by modifying the surface of Zna Mgb Alc -LDHs through a chemical etching method. The ultraviolet (UV) blocking properties of d-Zna Mgb Alc -LDHs were significantly improved, and d-Zn4 Al2 -LDH was added into asphalt to explore the potential anti–UV-aging application in asphalt. Research results show that 3 wt% of d-Zn4 Al2 -LDH could significantly improve the anti–UV-aging ability of asphalt, resulting from oxygen vacancy defects produced on the surface of d-Zn4 Al2 -LDH. Specifically, these oxygen defect vacancies can adsorb the free radicals generated during the asphalt aging process; therefore, it blocked the fragmentation of the macromolecule chain in asphalt and postponed the aging process. Graphical abstract: Image 1 Highlights: The defect-structured Zna Mgb Alc layered double hydroxides (LDHs) were prepared through a chemical etching method. The optimal sample (3 wt% of d-Zn4 Al2 -LDHs) exhibits significantly improved anti–UV-aging ability for asphalt. The reason for excellent performance is abundant oxygen vacancy defects produced on the surface of this efficient material.